Global Well-Posedness of the Inviscid Heat-Conductive Resistive Compressible MHD in a Strip Domain (Communications in Mathematical Research, 2021)
This paper concerns the inviscid, heat-conductive and resistive compressible MHD system in a horizontally periodic flat strip domain. The globalwell-posedness of the problem around an equilibrium with the positive constant density and temperature and a uniform non-horizontal magnetic fieldis established, and the solution decays to the equilibrium almost exponentially. Our result reveals the strong stabilizing effect of the transversal magnetic field and resistivity as the global well-posedness of compressible inviscidheat-conductive flows in multi-D is unknown.
Keywords: Compressible MHD; inviscid heat-conducting flow; magnetic diffusion; global well-posedness; strip domain.